The Implementation Of Politeness Strategies In Refusal By The Second Semester Students Of Muhammadiyah University In English Speaking Class - Nurjayanti, Nova; , Siti Zurhriah Ariatmi, M. Hum; , Nur Hidayat, M. Pd (2016)
This research aims at describing the use of politeness strategies in refusal conducted by English Department students. The study used descriptive qualitative research which includes thirty eight second-semester students at English Department of Muhammadiyah University of Surakarta. The data are refusal utterances collected by using Discourse Completing Task (DCT) as the instrument. The data are analyzed by using theory of politeness by Brown and Levinson and refusal strategy by Felix. The finding of the research are described in line with the problem statements. First, the research finding shows that direct refusal is most appeared refusal strategy which has value 46,2%. The second place is indirect refusal 43% and the last one is adjunct to refusal 10,8%. Second, the writer found that bald on record is the most appeared politeness strategy which has value 42,1%. The second place, there is positive politeness which has value 29,5%. The third place, there is negative politeness which has value 26,6% and the last one is off record which has value 1,8%. In using refusal, almost all participants use direct refusal instead of using indirect refusal or adjunct to refusal. Thus, the writer can conclude that the students do not master yet how to use refusal strategy politely.